"Extremely Rightful" Resistance: Land Appropriation and Rural Agitation in Contemporary Vietnam. Issue 3 (27th May 2019) - Chau, Lam Minh
ABSTRACT: Building on ethnographic fieldwork in a northern Vietnamese village, this article explores a rural protest against the appropriation of arable land for a development project. The focus is on villagers' collective memories of an exceptional protest staged in 2010. The aim of the protest was to pressure local district authorities to increase the compensation villagers agreed to take three years earlier. While originally accepting compensation when their holdings were appropriated to build an industrial park, they later considered that the compensation paid was unfair and that some funds were misappropriated. They were aware that the likelihood of getting additional compensation was small and the risk of repression high. In tracing their struggle, the article argues that villagers did not seek to retain land as their primary subsistence source or as cherished ancestral land. Neither were they driven by an abstract sense of justice. Rather, they represented themselves as active, responsible decision-makers, determined to risk their own safety to bring their family a better future. They therefore employed an "extremely rightful" form of resistance rarely documented in the scholarship on Asia. They not only confined actions within officially sanctioned channels, but also underplayed all oppositional intentions against central and local authorities.